The Potential of Using the Africanisation Framework to Improve Outcomes in the Artisanal and Small-Scale Mining Industry of Rustenburg, South Africa - Gloria Neo Tsipane; Neil Barnes (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Attempts to formalise artisanal and small-scale mining (ASM) have failed in most areas where illegal ASM occurs. The purpose of this study was to determine the role of Africanisation in promoting the formalisation of the ASM sector of South Africa. Due to the acute lack of employment and other challenges associated with ASM, it is essential to ensure that the sector is appropriately formalised to allow communities to benefit fully whilst minimising any negative impacts emerging from ASM. In this qualitative exploratory research, data was collected using semi-structured questionnaires from 15 participants and was analysed using thematic analysis. It was found that the over-reliance on capitalistic ideals in allocating mining opportunities is one of the main reasons why past formalisation attempts have failed to produce desired outcomes. This is probably because there is poor communication between the state and the mining communities, and this means the aspirations of the communities are not considered when creating mining policies. The researchers, therefore, proposed an alternative approach to govern the mining sector, and this approach takes advantage of the tendency of Africans to work as communities. This approach is based on the idea of Africanisation. Facilitating the exploitation of mineral resources by communities rather than individuals, as is the case in capitalistic societies, will help empower communities since the mining enterprises will benefit more individuals and proceeds from the mining enterprises will help stimulate local economic development.